The mediation role of schizotypal traits in the relationship between childhood trauma and earlier onset of panic disorder. Issue 4 (2nd October 2022) - Baygin, Cansu; Sevincok, Levent; Dogan, Bilge; Sevincok, Doga; Sair, Yasan Bilge
ABSTRACT: Objective: We hypothesized that, if childhood trauma is associated with schizotypal traits, schizotypal traits may mediate the relationship between childhood trauma and the earlier onset of panic disorder (PD). Methods: A total of 86 patients (49 females, 37 males), with PD aged between 18 and 65 years, were evaluated using the Panic and Agoraphobia Scale (PAS), the Schizotypal Personality Questionnaire-Brief (SPQ-B), and the Hamilton Anxiety Rating Scale (HARS). Results: The mean age was 38.7 ± 12.8 years (range = 19-65 years). Total scores of schizotypal traits (r = -0.41, p<0.001), and childhood trauma (r = -0.31, p = 0.004) were inversely correlated with age at onset of PD. There was a significant correlation between the severity of schizotypal traits and childhood trauma (r = 0.55, p<0.001). After the mediation analysis, the direct effect of childhood trauma on age at onset of PD was no longer significant (Exp(B) = -0.133, p = 0.273). The indirect coefficient for schizotypal traits was consistent with complete mediation (Exp(B) = -0.801, p = 0.001). Discussion: We suggest that schizotypal personality traits which are significantly associated with childhood trauma, may influence the onset of PD from early life.